2018
DOI: 10.1042/bst20170505
|View full text |Cite
|
Sign up to set email alerts
|

Control of pancreatic β-cell bioenergetics

Abstract: The canonical model of glucose-stimulated insulin secretion (GSIS) by pancreatic β-cells predicts a glucose-induced rise in the cytosolic ATP/ADP ratio. Such bioenergetic sensitivity to metabolic fuel is unusual as it implies that ATP flux is governed, to a significant extent, by ATP supply, while it is predominantly demand-driven in other cell types. Metabolic control is generally shared between different processes, but potential control of ATP consumption over β-cell bioenergetics has been largely ignored to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Uncoupled mitochondrial oxygen uptake is not controlled by ATP synthesis or ATP turnover, and thus generally reflects the capacity of cells for oxidizing fuel. The fuel oxidation capacity of INS-1E cells thus appears limited by the concentration of glucose ( Fig 2B ), which sits well with the glucose sensitivity of oxidative phosphorylation of pancreatic β-cells [ 46 , 47 ]. Cytokine exposure inhibits both coupled and uncoupled mitochondrial respiration ( Fig 2B ), which shows the respiratory inhibition emerges from a negative effect on glucose oxidation.…”
Section: Resultsmentioning
confidence: 82%
“…Uncoupled mitochondrial oxygen uptake is not controlled by ATP synthesis or ATP turnover, and thus generally reflects the capacity of cells for oxidizing fuel. The fuel oxidation capacity of INS-1E cells thus appears limited by the concentration of glucose ( Fig 2B ), which sits well with the glucose sensitivity of oxidative phosphorylation of pancreatic β-cells [ 46 , 47 ]. Cytokine exposure inhibits both coupled and uncoupled mitochondrial respiration ( Fig 2B ), which shows the respiratory inhibition emerges from a negative effect on glucose oxidation.…”
Section: Resultsmentioning
confidence: 82%
“…Here, the importance of metabolic control exerted by ADP stems from the simple fact that ADP must be reduced to low μM concentrations for KATP channels to close (Tarasov et al, 2006) and that mitochondrial ATP synthase cannot run without ADP (Chance and Williams, 1955). Transition between the 2 states is toggled by the large amount of ATP hydrolysis associated with membrane depolarization, pumps, and vesicle fusion (Nicholls, 2016;Affourtit et al, 2018). A key advantage of allosteric PK recruitment is the ability to reinforce metabolic oscillations in response to metabolic regulators like FBP (Merrins et al, 2013(Merrins et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Although many qualitative β-cell bioenergetics studies have shown that ADP supply and demand are critical for OxPhos and insulin secretion (Figure 6D and (Ainscow and Rutter, 2002;Doliba et al, 2003;Panten et al, 1986;Sweet et al, 2004;Affourtit et al, 2018)), quantitative metabolic control analyses in β-cells have remained lacking (Affourtit et al, 2018;Nicholls, 2016). Since tools to quantify the phosphorylation potential and ATP flux currently rely on temporal averaging (Affourtit et al, 2018), it is not yet possible to calculate the relative contribution of PK and OxPhos to KATP closure. We also lack the means to determine how PK-driven ATP/ADP cycling bioenergetically supports increased exocytosis relative to OxPhos.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that there are two key functions of complex I activation by CDK1 in ␤-cells beyond the ATP production required for the high bioenergetic demands of insulin biosynthesis, the maintenance of ionic gradients, and exocytosis (31,32). The first is redox disposal, i.e.…”
Section: Discussionmentioning
confidence: 99%